Mudanças estruturais na indústria brasileira: uma análise do período de 1995 a 2009 - Figueiredo, Helena Loiola de (2015)
The objective is to analyze the structural changes in the Brazilian industry between 1995 and 2009 considering its intersectoral relations. The structural causes of change were also identified in the industrial product, value added and employment in the industry; analyzed the evolution of linkages of industrial sectors; and checked the probabilities of change in the degree of linkages of these sectors. Such objectives are achieved with the use of input-output analysis via the method of structural decomposition; calculations of linkages index of Ghosh and Rasmussen / Hirschman; and the Markov chain method. From the data analysis it is evident that the structural changes in the industry, from the process of economic liberalization in the 1990s, were to weaken the intersectoral demand of the Brazilian economy. There was an industrial restructuring with increasing of the intermediate demands of intensive natural resources sectors while, especially the intensive scale sectors and with differentiated technology reduced their intermediate demands. The main relation proven in the study is that between 1995 and 2009 there was a reduction in the share of industry sectors in employment,value added and product and a growth service sectors. This transformation was stimulated by technological changes (structural changes in sectoral linkages) and changes in final demand. In such a way that changes in final demand were that most explained the employment growth, the value added growth and the product growth in the economy. In the other way the technological changes contributed to employment growth e value added growth, but reduced economy product in the period.